The Combinatory Effect of Spirulina Supplementation and Resistance Exercise on Plasma Contents of Adipolin, Apelin, Ghrelin, and Glucose in Overweight and Obese Men - Malekaneh Mohammad; Dehghani Karim; Mogharnasi Mehdi; Saghebjoo Marziyeh; Sarir Hadi; Nayebifar Shila (Hindawi Limited, 2022)
Introduction and Objective. Researchers are considering combining exercise and supplementation as a new strategy for weight loss and obesity prevention. This study is aimed at evaluating the effect of eight weeks of circuit resistance training and spirulina supplementation on plasma levels of adipolin, apelin, ghrelin, and glucose in overweight and obese men. Methods. The current investigation was conducted in a single-blind and quasiexperimental fashion. Sixty overweight and obese men (BMI>25) ranging in age from 30 to 55 years were purposefully selected and randomly assigned to one of four groups: training plus spirulina (T+S), training plus placebo (T+P), spirulina (S), or placebo (P). For eight weeks, the (S) and (P) groups consumed two 500 mg spirulina and placebo capsules daily, respectively. Resistance training was performed three sessions a week over eight weeks, consisting of 12 movements with 1-, 2-, 3-, and 4-minute rest intervals and 40-90 percent maximal repetition. Adipolin, apelin, and ghrelin indices were measured before and after exercise using special kits. Results. All variables changed significantly between groups except for apelin. Within-group comparisons revealed a substantial increase in adipolin levels in the (T+S) and (T+P) groups (P<0.05). Apelin levels were decreased in the (T+S) and (T+P) groups. Additionally, FBS levels reduced significantly in (T+S) (P=0.01). Conclusion. It seems that eight weeks of circuit resistance training and spirulina supplementation can lead to reduced weight and apelin and FBS levels as well as increased concentrations of adipolin and ghrelin contents in overweight and obese men.